Regulation of the DLC3 tumor suppressor by a novel phosphoswitch - Yannick Frey; Cristiana Lungu; Florian Meyer; Franziskus Hauth; Daniel Hahn; Corinna Kersten; Vivien Heller; Mirita Franz-Wachtel; Boris Macek; Igor Barsukov; Monilola A. Olayioye (iScience, 2024)
Summary: Deleted in liver cancer 3 (DLC3) is a Rho GTPase-activating protein (RhoGAP) that plays a crucial role in maintaining adherens junction integrity and coordinating polarized vesicle transport by modulating Rho activity at the plasma membrane and endomembranes. By employing bioinformatical sequence analysis, in vitro experiments, and in cellulo assays we here identified a polybasic region (PBR) in DLC3 that facilitates the association of the protein with cellular membranes. Within the PBR, we mapped two serines whose phosphorylation can alter the electrostatic character of the region. Consequently, phosphomimetic mutations of these sites impaired the membrane association of DLC3. Furthermore, we found a new PBR-dependent localization of DLC3 at the midbody region, where the protein locally controlled Rho activity. Here, the phosphorylation-dependent regulation of DLC3 appeared to be required for proper cytokinesis. Our work thus provides a novel mechanism for spatiotemporal termination of Rho signaling by the RhoGAP protein DLC3.